Intraspecific phylogeny of a Patagonian fescue: differentiation at molecular markers and morphological traits suggests hybridization at peripheral populations - Guidalevich, Verónica (2023)
Background and Aims: Grasses of the Festuca genus have complex phylogenetic relations due to morphological similarities among species and interspecific hybridization processes. Within Patagonian fescues, information concerning phylogenetic relationships is very scarce. In Festuca pallescens, a widely distributed species, the high phenotypic variability and the occurrence of interspecific hybridization preclude a clear identification of the populations. Given the relevance of natural rangelands for livestock production and their high degradation due to climate change, conservation actions are needed and knowledge about genetic variation is required. Methods: To unravel the intraspecific phylogenetic relations and to detect genetic differences, we studied 21 populations of the species along its natural geographical distribution by coupling both molecular [internal transcribed spacer (ITS) and trnL-F markers] and morpho-anatomical analyses. Bayesian inference, maximum likelihood and maximum parsimony methods were applied to assemble a phylogenetic tree, including other native species. The morphological data set was analysed by discriminant and cluster analyses. Key Results: The combined information of the Bayesian tree (ITS marker), the geographical distribution of haplotype variants (trnL-F marker) and the morpho-anatomical traits, distinguished populations located at the margins of the distribution. Some of the variants detected were shared with other sympatric species of fescues. Conclusions: These results suggest the occurrence of hybridization processes between species of the genus at peripheral sites characterized by suboptimal conditions, which might be key to the survival of these populations.